Impacto da interferência da rede primária sobre o desempenho de outage de uma rede cooperativa-cognitiva com seleção de retransmissores full duplex - Dourado, Silvio César Vicentim [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The performance of a cooperative-cognitive network that operates under the interference effect generated by a primary network is analyzed in terms of the outage probability. The cooperative-cognitive network is composed of a source, multiple relays and a destination, which operate under the interference generated by multiple primary transmitters and a primary receiver, using the underlay spectral sharing technique. It is considered that the relays operate under the decode-and-foward protocol and full duplex relaying mode. Four relay selection criteria are considered to evaluate the cooperativecognitive network performance: (i) opportunistic criterion, which selects the relay that maximizes the end-to-end signal-noise-ratio (SNR) of the system; (ii) partial relay selection based on first-hop links, which selects the relay that maximizes the signal-to-noise-plus-interference ratio (SINR) of the first hops; (iii) partial relay selection based on second-hop links, which selects the relay that maximizes SINR of the second hops; and (iv) partial relay selection based on self-interference links, which selects the relay that minimizes SNR of the self-interference links. For these criteria, the combined effect of the interference generated by the primary transmitters, the interference temperature, the self-interference at the relays, and the number of relays is evaluated over the cooperative-cognitive network performance. Numeric Monte Carlo simulations are used to evaluate the network performance. Furthermore, analytical expressions are obtained for the asymptotic outage probability for all selection relay criteria, which are validated through the results obtained by numeric simulations.

O desempenho de uma rede cooperativa-cognitiva que opera sob o efeito de interferência gerada por uma rede primária é avaliado em termos da probabilidade de outage. Considera-se que a rede cooperativa-cognitiva consiste de uma fonte, múltiplos retransmissores e um destino, os quais operam sob a presença de múltiplos transmissores primários e um receptor primário, usando a técnica de compartilhamento de espectro do tipo underlay. Considera-se ainda que os retransmissores operam sob o protocolo decodifica-e-encaminha e em modo de retransmissão full duplex. O desempenho da rede secundária foi avaliado para quatro critérios de seleção de retransmissor: (i) critério oportunista, que escolhe o retransmissor que maximiza a relação sinal-ruído (SNR) fim-a-fim do sistema; (ii) critério parcial do primeiro salto, que escolhe o retransmissor que maximiza a relação sinal-interferênciamais- ruído (SINR) do primeiro salto; (iii) critério parcial do segundo salto, que seleciona o retransmissor que maximiza a SINR do segundo salto; e (iv) critério parcial do enlace de autointerferência, que seleciona o retransmissor que minimiza a SNR do enlace de autointerferência. Para esses critérios, avalia-se o efeito combinado sobre o desempenho do sistema da interferência provocada pelos transmissores primários, da temperatura de interferência tolerada pelo receptor primário, da autointerferência dos retransmissores, bem como do número de retransmissores. Simulações numéricas utilizando o método de Monte Carlo são implementadas para avaliar o desempenho. Além disso, uma análise da probabilidade de outage assintótica para todos os critérios de seleção é desenvolvida e confrontada com os resultados obtidos das simulações numéricas, a fim de validá-las.
Impact of primary network interference on the outage performance of a cooperative-cognitive network with selection of full duplex relays
Keywords: Comunicações digitais; Sistemas de comunicação sem fio; Telecomunicações